On Transient Response of Piezoelectric Transducers - Fa, Lin; Mou, Jinpeng; Fa, Yuxiao; Zhou, Xin; Zhang, Yandong; Liang, Meng; Ding, Pengfei; Tang, Shaojie; Yang, Hong; Zhang, Qi; Wang, Maomao; Li, Guihui; et al. (Frontiers in Physics, 2018)
In this paper, we report a new model in analysis of spherical thin-shell piezoelectric transducers for transient response, based on Fourier transform and the principle of linear superposition. We show that a circuit-network, a combination of a series of parallel-connected equivalent-circuits, can be used in description of a spherical thin-shell piezoelectric transducer. When excited by a signal with multiple frequency components, each circuit would have a distinctive radiation resistance and a radiation mass, arising from an individual frequency component. Each frequency component would act independently on the electric/mechanic-terminals. A cumulative signal-output from the mechanic/electric-terminals is measured as the overall acoustic/electric output. As a prototype example in testing the new model, we have designed two spherical shin-shell transducers, applied a gated sine electric-signal as the initial excitation, and recorded the experimental information. The transient response and the output signals are calculated based on the new model. The results of calculation are in good agreement with that of experimental observation.